Literasi Statistik Dalam Pembelajaran Matematika SD Melalui Kurikulum 2013 - Alman Alman; Tatang Herman; Sufyani Prabawanto; Yeni Dwi Kurino (Elementary Teacher Education Program, Majalengka University, 2023)
This research aims to investigate the implementation of statistical literacy at the elementary schools level within the mathematics curriculum. Statistical literacy is a essential skill that enables students to understand, analyze, and interpret data and information critically. In an era where information and data are abundant, having statistical literacy skills has become increasingly relevant and crucial for developing students' understanding of the world, which involves various data-based information. This study uses a qualitative approach by analyzing government regulation documents concerning the mathematics curriculum used at the elementary school level. The results of the research indicate that statistical literacy has not been fully integrated effectively into the elementary school mathematics curriculum. While there have been some efforts to incorporate statistical concepts into mathematics learning, there are still challenges in teaching data analysis skills and interpreting statistical information more deeply.